IDENTIFIKASI PERSYARATAN PELANGGAN TERHADAP PRODUK TAHU - Millatul Ulya (Agroindustrial Technology, University of Trunojoyo Madura, 2012)
Tofuindustriesmust producea qualified tofuthat can meetcustomersatisfactionto surviveintoday's businesscompetition. Therefore, itshould be identifiedof customer requirementsand the level ofpriorityfortofuproducts, so thattofu industriescan producetofuin line withcustomer expectations. This study aimed toidentify thecustomer requirements to the tofu productanddetermineprioritiesof customerrequirements. Results showed that8 (eight) requirements of customersintofuproductsthattaste,smell, texture, color, nutritional content, product safety, shelf life, and price. The most important attributewas3 thatsmell, textureand product safety. Whilethe otherfive attributes'important' to be filledtofuproducers. The results ofthis research canbe continuedtodeveloptechnicalresponsesfortofuindustriestomeetcustomersatisfaction